1995
DOI: 10.5032/jae.1995.03034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Of The Adoption Of Sustainable Agriculture Practices: Implications For Agricultural Education

Abstract: The study sought to determine the perceptions of selected farmers on issues related to sustainable agriculture practices. The study found farmers were positive about sustainable agriculture practices but still had several concerns about some practices within the concept. Farmers were trying several different practices and were open to experiment with new ideas. Most farmers appeared to be at an information gathering stage. The process of education used at this point in decision-making about new practices could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 10 publications
3
55
0
2
Order By: Relevance
“…To refine analyses, relative advantage is split into three independent factors: time demands, costs and risks (Sattler et al, 2010). Compatibility refers to the degree of change required to assimilate an innovative practice into an individual's routines (Rogers, 2003), or its consistency with the potential users' existing values, experiences and needs, which are important factors for the adoption of technologies (Alonge et al,1995;Westra et al, 1997). Complexity refers to the anticipated difficulty in understanding and applying an innovation.…”
Section: Survey Designmentioning
confidence: 99%
“…To refine analyses, relative advantage is split into three independent factors: time demands, costs and risks (Sattler et al, 2010). Compatibility refers to the degree of change required to assimilate an innovative practice into an individual's routines (Rogers, 2003), or its consistency with the potential users' existing values, experiences and needs, which are important factors for the adoption of technologies (Alonge et al,1995;Westra et al, 1997). Complexity refers to the anticipated difficulty in understanding and applying an innovation.…”
Section: Survey Designmentioning
confidence: 99%
“…Having tested the questionnaire for validity and reliability it was filled out by researcher and then the collected data were analyzed. Farmers' perceptions towards sustainable agricultural technologies were operationalized as the extent of their agreement with the statements related to 10 selected indicators of sustainable agriculture which were obtained from review of literature [1,4,5,7,9,13,14,16,22,31,35] . With consideration to rice cropping system's situation, the selected indicators of sustainable agriculture included negative effects of agrochemicals on environment and human health, reduced use of agrochemicals in agriculture, use of organic (animal and green) manure, retaining crop remains and wastes on farm after harvesting, low tillage, crop rotation and farm diversification, cultivation of legume after rice harvesting, biologic and agronomic control of pests.…”
Section: Methodsmentioning
confidence: 99%
“…Smathers [33] concluded in his study that, it was likely that the successful adoption of conservation practices would be influenced by a farmer's attitude and perceptions, than any other factor. Alonge and Martin [1] , found that farmer's perceptions regarding the compatibility of sustainable practices with their farming systems emerged as the best predictors of adoption of such practices. Sheikh et al [32] found that attitude towards the use of technology and contact with extension agents were the main factors influencing the adoption of no-tillage practice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations